ATP- and Adenosine-Mediated Signaling in the Central Nervous System: Chronic Pain and Microglia: Involvement of the ATP Receptor P2X4 - Kazuhide Inoue; Makoto Tsuda; Schuichi Koizumi (Elsevier, 2004)
We have been studying the role of ATP receptors in pain and already reported that activation of P2X2/3 heteromeric channel/receptor in primary sensory neurons causes acutely tactile allodynia, one hallmark of neuropathic pain. We report here that tactile allodynia under the chronic pain state requires an activation of the P2X4 ionotropic ATP receptor and p38 mitogen-activated protein kinase (MAPK) in spinal cord microglia. Two weeks after L5 spinal nerve injury, rats displayed a marked mechanical allodynia. In the rats, activated microglia were detected in the injured side of the dorsal horn and the level of the dually-phosphorylated active form of p38MAPK (phospho-p38MAPK) in these microglia was increased. Moreover, intraspinal administration of a p38MAPK inhibitor, SB203580, suppressed the allodynia. We also found that the expression level of P2X4 was increased strikingly in spinal cord microgila after nerve injury and that pharmacological blockade or inhibition of the expression of P2X4 reversed the allodynia. Taken together, our results demonstrate that activation of P2X4 or p38MAPK in spinal cord microglia is necessary for tactile allodynia after nerve injury. Keywords:: ATP receptor, P2X4, microglia, p38 mitogen-activated protein kinase, allodynia